Experimental and numerical study of radial lateral fracturing for coalbed methane. (9th September 2015) - Fu, Xuan; Li, Gensheng; Huang, Zhongwei; Liang, Yuesong; Xu, Zhengming; Jin, Xiao
Abstract: Drilling ultra-short radius horizontal laterals in a vertical well and then operating hydraulic fracturing (radial lateral fracturing, abbreviated as RLF) is proposed as a prospective novel method to increase the single-well productivity for coalbed methane (CBM) development. The objective of this article is to find the best fracture network profile RLF can generate and what kind of formation is suitable for this fracturing technique. Experiments using a true tri-axial fracturing simulation system are designed to analyse the influence of different lateral length, count and azimuth on the fracturing initiation and propagation. A numerical simulation is also carried out to study the sensitivity of the coal integrity and in situ stress state on the fracture initiation type. Our work shows that: the best effect of RLF is achieved when it initiates from the bedding plane where the laterals lie and forms a fracture network with one main horizontal fracture connecting multiple vertical fractures; the breakdown and injection pressure will be decreased by increasing the lateral length and count; increasing the lateral length can enlarge the horizontal fracture area; the optimal lateral design for horizontal initiation is four laterals with the phase of 90° and each lateral is at 45° from the horizontal stress; RLF is suitable for the intact coal seams in which cracks or cleats are not well developed and the overburden stress should be close to or less than the maximum horizontal stress. This paper will provide the experimental support and theoretical bases for CBM RLF design.